Bear bones: Burr Lafayette Mystery # 3 - Cutter, Charles 1951- (Charles A.) (Traverse City, MI : Mission Point Press, 2020)
"Helen Lockwood's boat was found drifting off Sleeping Bear Dunes with no one aboard. A year later, her body was found in a shallow grave on South Manitou Isalnd. She had been in court, fighting with the National Park Service, which was trying to take her family's four-hundred-acre cherry orchard for the new national park. Burr Lafayette, recently divorced and the deposed head of a major Detroit law firm, had kept the Park Service at bay for seven years. But now Helen's husband, Tommy, is arrested for her murder. It seems he had been trying to sell the orchards to the Park Service ever since Helen went missing. All the evidence points to Tommy, but there's no shortage of suspects. A man at loose ends, Burr is a brilliant litigator who prefers sailboats and dogs over courtrooms and clients. He's not a criminal lawyer, but he's convinced there is a clue somewhere in teh dunes that will unlock the truth." --back cover.
new book 2024 spring.
Keywords: Murder -- Investigation -- Fiction; Eminent domain -- Fiction; Orchards -- Michigan -- Fiction; Sleeping Bear Dunes National Lakeshore (Mich.) -- Fiction; Detective and mystery fiction; Legal fiction; Detective fiction; Mystery fiction